2019
DOI: 10.1055/s-0039-1697975
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pulmonary Exacerbations in Cystic Fibrosis

Abstract: With the improving survival of cystic fibrosis (CF) patients and the advent of highly effective cystic fibrosis transmembrane conductance regulator therapy, the clinical spectrum of this complex multisystem disease continues to evolve. One of the most important clinical events for patients with CF in the course of this disease is an acute pulmonary exacerbation. Clinical and microbial epidemiology studies of CF pulmonary exacerbations continue to provide important insight into the disease course, prognosis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
48
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 141 publications
0
48
0
3
Order By: Relevance
“…[17] The occurrence of respiratory exacerbations are associated with an accelerated decline in lung function and reduced quality of life and survival. [15][16][17] On the other hand mean values of FEV1 in the analysed patients, presented stable results during at least 3 years of observation; there was no difference between Groups. This may be due to the age -below 8 -too early to identify signi cant differences in FEV1 secondary to clinical outcome (such as pulmonary exacerbations, bacterial colonisations), which likely takes longer to cause impairment of lung function that is identi able with spirometry.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…[17] The occurrence of respiratory exacerbations are associated with an accelerated decline in lung function and reduced quality of life and survival. [15][16][17] On the other hand mean values of FEV1 in the analysed patients, presented stable results during at least 3 years of observation; there was no difference between Groups. This may be due to the age -below 8 -too early to identify signi cant differences in FEV1 secondary to clinical outcome (such as pulmonary exacerbations, bacterial colonisations), which likely takes longer to cause impairment of lung function that is identi able with spirometry.…”
Section: Discussionmentioning
confidence: 75%
“…It is very bene cial observation due to reports which emphasise that the repeated mildto-moderate pulmonary exacerbations especially in the rst years of life result in airway remodelling, while more severe hospitalised episodes could increase structural airway injury risk. [13][14][15][16] Data from Australia showed improved survival in future in patients with lower number of hospitalisations in the rst 3 years of life. [17] The occurrence of respiratory exacerbations are associated with an accelerated decline in lung function and reduced quality of life and survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing the tomography of September 2019 with the tomography of April 2020 (Fig. 2), we found that both present chronic lesions typical of cystic fibrosis and patches of ground glass patches of subpleural distribution in the basal lobes, which corresponds to the process chronic inflammatory 2,9,15 .…”
Section: Discussionmentioning
confidence: 95%
“…It is recognized that viral infections in patients with cystic fibrosis are a factor of poor prognosis and deterioration of lung function and increased frequency of PE and its severity 2,7,9,10 . The symptoms of a SARS-CoV-2 infection differ from the symptoms of PE that most patients with cystic fibrosis know how to recognize 5,7 .…”
Section: Discussionmentioning
confidence: 99%